Financial Innovation, Economic Growth and Sustainable Development in an Emerging Market: Nigeria - Olugbenga Adeshola Olunuga; Mustapha Babatunde Ademola Ashoghon (Emerging Markets Journal)
This paper presents recent studies on the effects of financial innovation on economic growth and sustainable development in Nigeria. The financial sectors worldwide are becoming increasingly important and competitive. Therefore, in order to compete successfully, it is necessary to possess flexibility and adaptability to change, as well as a willingness to embrace innovation. Financial markets are becoming more advanced and complex due to financial innovation, which helps direct capital towards productive sectors that are necessary for economic growth and development. The study employed time series data. Statistical data analysis techniques were employed to evaluate the secondary data on financial innovation. Research indicates that financial innovation has a significant impact on both economic growth and sustainable development in Nigeria. The study found that financial innovation variables have a positive effect. Therefore, financial institutions should prioritize easy and secure access to financial services when developing their financial innovation strategies. Regulatory bodies, on the other hand, should establish a regulatory environment that promotes innovative solutions capable of influencing economic growth and sustainable development.